A Critical Assessment of Computer-Aided Approaches for Identifying FAK Inhibitors - Quispe Castillo, Patricia Araceli (2025)
Focal Adhesion Kinase (FAK) is a key regulator of tumor cell migration and survival, and its persistent overexpression in aggressive cancers has motivated ongoing efforts to identify novel small-molecule inhibitors. Despite this interest, progress in discovering new potent scaffolds has been limited. In this work, we applied a multistep computational workflow followed by experimental testing to refine hit selection and reduce the false positives typically associated with docking. DrugBank and several commercial libraries were screened using Exponential Consensus Ranking (ECR) docking, and molecular dynamics simulations were used to assess pose stability and interaction persistence. A subset of predicted binders was then tested in MG-63 (bone cancer) and MDA-MB-231 (breast cancer) cells using cell viability and wound-healing assays, followed by direct autophosphorylation assays with recombinant FAK. Several repurposed compounds, including clofazimine and tafamidis, produced clear dose-dependent effects on cell migration, although their inhibitory activity in biochemical assays remained weak (IC50 values above 100 μM), far from the potency of the reference inhibitor TAE226. Retrospective analysis of the computational workflow showed that standard MM-GBSA calculations did not correlate with these experimental outcomes. However, incorporating explicit water molecules through the NWAT-MMGBSA approach improved agreement with the biochemical data and helped to rationalize the limited affinity observed experimentally. Taken together, the results underline the relevance of explicit solvation in modeling the FAK active site and suggest that refined solvent-aware protocols may provide more reliable guidance for future screening efforts.